Deep extreme learning machine with knowledge augmentation for EEG seizure signal recognition - Zhang, Xiongtao; Dong, Shuai; Shen, Qing; Zhou, Jie; Min, Jingjing (Frontiers in Neuroinformatics, 2023)
Intelligent recognition of electroencephalogram (EEG) signals can remarkably improve the accuracy of epileptic seizure prediction, which is essential for epileptic diagnosis. Extreme learning machine (ELM) has been applied to EEG signals recognition, however, the artifacts and noises in EEG signals have a serious effect on recognition efficiency. Deep learning is capable of noise resistance, contributing to removing the noise in raw EEG signals. But traditional deep networks suffer from time-consuming training and slow convergence. Therefore, a novel deep learning based ELM (denoted as DELM) motivated by stacking generalization principle is proposed in this paper. Deep extreme learning machine (DELM) is a hierarchical network composed of several independent ELM modules. Augmented EEG knowledge is taken as complementary component, which will then be mapped into next module. This learning process is so simple and fast, meanwhile, it can excavate the implicit knowledge in raw data to a greater extent. Additionally, the proposed method is operated in a single-direction manner, so there is no need to perform parameters fine-tuning, which saves the expense of time. Extensive experiments are conducted on the public Bonn EEG dataset. The experimental results demonstrate that compared with the commonly-used seizure prediction methods, the proposed DELM wins the best average accuracies in thirteen out of the twenty-two data and the best average F-measure scores in ten out of the twenty-two data. And the running time of DELM is more than two times quickly than deep learning methods. Therefore, DELM is superior to traditional and some stateof-the-art machine learning methods. The proposed architecture demonstrates its feasibility and superiority in epileptic EEG signal recognition. The proposed less computationally intensive 1 Sample et al. deep classifier enables faster seizure onset detection, which is showing great potential on the application of real-time EEG signal classification.